Transformative Learning Management: Building Students’ Critical Awareness - Muhammad Eko Arief Wijaksono; Muhammad Munif; Umar Manshur; Unzilah Khomairotus Shiyamah; Suhermanto; Putri Fahmadia Dinda Maulida Thohir (Journal of Educational Management Research, 2024)
This study aims to explore the implementation of transformative learning management in building students’ critical awareness in secondary education environments. The transformative approach is considered capable of creating a learning space that not only focuses on mastering the material but also on changing students’ way of thinking about the social reality around them. This study employs a qualitative method with a case study approach in one secondary school that implements a transformative learning model. Data were collected through classroom observations, in-depth interviews with teachers and students, and analysis of curriculum documents and lesson plan implementation. The results of the study indicate that learning strategies that integrate reflective discussions, contextual issue analysis, and active student empowerment can improve critical thinking skills, social empathy, and student participation in local community issues. The implications of these findings underscore the importance of teacher training in a critical pedagogical approach, as well as the need for school policy support in adopting a more humanistic and participatory curriculum. This study recommends the development of a structured transformative learning management model to improve the quality of meaningful learning.